Effect of an oral bovine colostrum supplement (intact TM) on running performance - Buckley, J.; Abbott, M.; Martin, S.; Brinkworth, G.; Whyte, P. (1998)
This is an abstract from: 1998 Australian Conference of Science and Medicine in Sport, Adelaide, South Australia, October 1998. The present study employed a double-blind, placebo controlled, parallel, randomised design to determine the effect of supplementation with a low fat, low lactose, concentrated bovine colostrum protein powder (intactä , NorthField Laboratories Pty Ltd) on plasma IGF-1 concentrations and endurance running performance. The results of this study indicate that oral supplementation with intact TM bovine colostrum improves the ability to perform a second bout of maximal exercise following a relatively short period of recovery from a prior bout of maximal exercise.